2016
DOI: 10.1002/app.44150
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitive antibacterial and cytotoxicity performances of a TiO2/carboxymethyl chitosan/poly(vinyl alcohol) nanocomposite hydrogel by in situ radiation construction

Abstract: Nano‐TiO2/carboxymethyl chitosan (CMCS)/poly(vinyl alcohol) (PVA) ternary nanocomposite hydrogels were prepared by freezing–thawing cycles and electron‐beam radiation with PVA, CMCS, and nano‐TiO2 as raw materials. The presence of nano‐TiO2 nanoparticles in the composite hydrogels was confirmed by thermogravimetry, Fourier transform infrared spectroscopy, and X‐ray powder diffraction. Field emission scanning electron microscopy images also illustrated that the TiO2/CMCS/PVA hydrogel exhibited a porous and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Longo et al [82] explained that TiO 2 could be present or trapped on the composite surface, thus enhancing their antimicrobial activity due to the generation of electron-hole pairs without the need of light-induced radiation (Figure 3b). Similar results were reported by Li et al [81] and Xiao et al [6] using a CS-Ag-TiO 2 composite against E. coli, S. aureus, P. aureginosa, and C. albicans, probably for the synergistic effect of the three components, which suggests that microbial inactivation is linked with electrostatic interactions between the cell membranes and the composite, followed by oxidative stress caused by photo-generated reactive radicals, causing cell death (Figure 3d).…”
Section: Antimicrobial Activitysupporting
confidence: 87%
See 1 more Smart Citation
“…Longo et al [82] explained that TiO 2 could be present or trapped on the composite surface, thus enhancing their antimicrobial activity due to the generation of electron-hole pairs without the need of light-induced radiation (Figure 3b). Similar results were reported by Li et al [81] and Xiao et al [6] using a CS-Ag-TiO 2 composite against E. coli, S. aureus, P. aureginosa, and C. albicans, probably for the synergistic effect of the three components, which suggests that microbial inactivation is linked with electrostatic interactions between the cell membranes and the composite, followed by oxidative stress caused by photo-generated reactive radicals, causing cell death (Figure 3d).…”
Section: Antimicrobial Activitysupporting
confidence: 87%
“…They also stated that a GO-CS-TiO 2 composite can selectively increase the permeability of microbial cell membranes, promoting a leakage of cell contents, mainly by the direct physical interaction between the GO-CS-TiO 2 composite and the microorganisms. Additionally, it has been reported that nano-TiO 2 /CS/PVA ternary composite exhibited enhanced antimicrobial activity against E. coli and S. aureus than the individual components [81].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Recently, photosensitive antibacterial TiO 2 -NPs/CMCh/PVA ternary nanocomposite hydrogels have been reported [ 170 ]. Nanocomposite hydrogels were prepared by freezing-thawing cycles and electron-beam radiation with PVA, CMCh and TiO 2 -NPs as raw materials.…”
Section: Antimicrobial Hydrogels Containing Metal Oxide Nanoparticmentioning
confidence: 99%
“…They found that the antibacterial rate initially increases and then gradually decreases as the quality fraction of CMCS increases. The maximum antibacterial rate can be 98.63% when the mass fraction of CMCS is 20% . Kim et al prepared a thermosensitive methylcellulose hydrogel containing AgNPs via one-pot synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum antibacterial rate can be 98.63% when the mass fraction of CMCS is 20%. 22 Kim et al prepared a thermosensitive methylcellulose hydrogel containing AgNPs via one-pot synthesis. In spite of the type of bacteria, asprepared hydrogels show an excellent antibacterial rate of 99.9% when the initial bacterial concentration is 2 × 10 5 CFU/ mL.…”
Section: Introductionmentioning
confidence: 99%